Institutional analysis of Apo Island protected landscape and seascape Dauin, Negros Oriental, Philippines - Lizada, Joy C. (2003)
Apo Island was declared Protected Landscape and Seascape under the NIPAS Act of 1992 to ensure the preservation, conservation and development of its natural resources and environment. This paper described the past and present interventions in the Island since conservation initiatives started in 1979 with Siliman University. Both primary and secondary data pertaining to the development and maintenance of AIPLS were used in the study. Key informants comprising of selected residents of Apo Island, government officials at the barangay, municipal, provincial and regional levels, representatives from NGOs as well as owners/managers of resorts and dive tour operators in Apo Island and Municipality of Dauin were interviewed. Efforts were made to ensure that the views of a wide variety of stakeholders were reflected in the study. Issues and concerns of Apo Island as a protected landscape and seascape were identified and analyzed given the existing institutional arrangements in the island; namely, organizational and functional arrangements, absence of the management plan and fund management. Recommendations included, among others, the formulation of a management plan; the restructuring of the organizational set-up; and the streamlining of financial procedures and fund management.
Keywords: Apo Island (Dauin, Negros Oriental)